The Manipulation of Retail Traders by Market Makers : An Empirical Case from Indonesia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This paper aims to investigate who the market makers are and how they are manipulating retail traders in the Indonesian Stock Exchange. The method used is library research and field research. The approach to this research is a descriptive approach because it wants to describe the empirical reality behind the phenomenon in depth. Information data uses primary data, namely conducting interviews and secondary data which is data that is available through journals, books and other factual supporting sources. Apart from that, analysis of the information data used uses the Miles & Huberman Interactive Analysis Model starting from data collection, data reduction, data presentation and drawing conclusions. Stock observation observation method through the stockbit application, to see stock movements over the current 3 (three) year period. Fried stocks are one of the stocks that can provide fast returns in the blink of an eye. To transact in fried stocks, someone must have an aggressive risk profile and already have a lot of experience in the world of stocks. The share price had an extraordinary increase, this was caused by the Market Maker deliberately manipulating the share price.